Clinical effects of balofloxacin on dental and oral surgical infectious diseases - Yamane, Nobuo; Naitoh, Hiroyuki; Morihana, Takefumi; Kato, Hisashi; Yamamoto, Tadashi; Kanno, Kazuyuki; Tomita, Fumisada; Kaneko, Akihiro; Busujima, Yasunobu; Sasaki, Jiro; Shiiki, Kazuo; Karakida, Kazunari; et al. (Japanese Journal of Chemotherapy, 1995)
The clinical effects of a new oral quinolone, balofloxacin (BLFX), on infectious diseases in the fields of dentistry and oral surgery were investigated. The subjects were 156 patients (75 males and 81 females) consisting of 63 with periodontitis, 41 with pericoronitis and 52 with osteitis of jaw. With the exception of 10 severe cases, the infectious diseases were mild (75 patients) or moderate (71 patients). The patients were given the drug at a daily dose of 200 mg (in 2 divisions or at one time) or 400 mg (in 2 divisions) for 3-12 days. According to the Drug Efficacy Criteria, the efficacy rate was 82.5%(52/63) for periodonitis, and 87.8%(36/41) for pericoronitis and 94.2%(49/52) for osteitis of jaw, for an overall efficacy rate of 87.8%. The efficacy rate was not influenced by the severity of infectious symptoms, the presence or absence of surgical treatment, or daily dose. The pyogenic bacteria isolated from 67 patients with closure abscess included 109 strains, consisting of 52 strains of aerobic grampositive bacteria, 8 strains of aerobic gram-negative bacteria and 49 strains of anaerobic bacteria. 100 (91.7%) of the 109 isolates were eradicated by BLFX treatment. Mild gastrointestinal symptoms, headache and drug eruption appeared as adverse events in 7 patients (4.4%), but all improved rapidly after the discontinuation of administration. Slight eosinophilia was observed in five patients and elevated LDH in one, as abnormal changes in clinical laboratory test values, but none were especially problematic in terms of safety.